Penanganan Tindak Pidana Viral: Reduksi Terhadap Asas Legalitas Ke Asas Viralitas - Muammar, Muammar (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2023)
Introduction: The handling of a number of criminal cases that have befallen victims and reported to the police, must first meet a number of dead ends. The justice that the victim expects from the case that happened to him must wait until the case goes viral and creates a reaction and public pressure. Purposes of the Research: This study aims to answer how to reduce and shift the principle of legality to the principle of